Intrapulmonary vascular dilatation evaluated by 99mTc-MAA scintigraphy and its association with portal hypertension in schistosomiasis. - Andréa Simone Siqueira de Queirós; Simone Cristina Soares Brandão; Ana Lúcia Coutinho Domingues; Liana Gonçalves Macedo; Maira Souto Ourem; Edmundo Pessoa Almeida Lopes (PLoS Neglected Tropical Diseases, 2014)
BACKGROUND: Portal hypertension is responsible for various complications in patients with schistosomiasis, among them intrapulmonary vascular dilations (IPVD). In cirrhotic patients the presence of IPVD is a sign of poor prognosis, but in patients with hepatosplenic schistosomiasis (HSS) there are no studies assessing the significance of this change. The aim of this study was to evaluate the occurrence of IPVD through 99mTc-MAA scintigraphy in patients with HSS and its relationship with clinical, laboratory, endoscopic and ultrasound parameters. METHODS: Cross-sectional study evaluating 51 patients with HSS. Patients were diagnosed with IPVD when the brain uptake of 99mTc-MAA was higher than 6%. Subsequently, they were divided according to presence (G1) or absence (G2) of IPVD and variables were compared between groups. RESULTS: Overall, 51 patients with mean age of 56±12 years were assessed. IPVD was observed in 31 patients (60%). There was no statistically significant differences between groups when clinical, laboratory and endoscopic parameters were compared. Regarding ultrasound parameters, the splenic vein diameter was smaller in G1 (0.9 ± 0.3 cm) compared to G2 (1.2 ± 0.4 cm), p=0.029. CONCLUSION: In patients with HSS, the occurrence of IPVD by 99mTc-MAA scintigraphy was high and was associated with lower splenic vein diameter, which can be a mechanism of vascular protection against portal hypertension. However, more studies are needed to determine the clinical significance of the early diagnosis and natural evolution of IPVD in this population.